Health and Development. (Pamphlet Series; Pamphlet Series, No., 2004)
The past century has been marked by rapid advances in human welfare. People in most parts of the world are healthier and are living longer. While this trend is likely to continue, hopes are fading in some regions where progress slowed or stopped in the1990s, primarily as a result of the AIDS epidemic. This compilation of articles published over the past five years in the pages of F and D looks at the important links between health and economic progress. Articles range over a variety of topics, from the Millennium Development Goals and their health-related targets for 2015 to the economics of tobacco control. Several articles examine the impact of AIDS and the global reaction, while others look at debt and the intellectual property aspects of health care.